Research on the Generation Mechanism and Optimization Strategy of Online International Chinese Teacher Institutions from the Perspective of Ecosystem - WU, YI; Gaikwad, Sophia Sandeep (Journal of Ecohumanism, 2024)
Based on the perspective of ecosystem theory, this study deeply explores the generation mechanism and optimization path of online international Chinese teacher institutions. The study focuses on the interactive relationship between various elements in the online education ecosystem. It adopts a combination of qualitative research and quantitative analysis to systematically investigate the operation mode, teacher construction, curriculum development, and technical support of online international Chinese teacher institutions. The study found that the sustainable development of online international Chinese teacher institutions is affected by the synergistic effect of internal ecological elements and the external ecological environment. Based on the results of empirical research, this paper proposes a strategic framework for optimizing the ecosystem of online international Chinese teacher institutions, including building a multi-level training system, innovating curriculum design methods, improving technical support platforms, and strengthening quality supervision mechanisms, etc., to provide theoretical basis and practical guidance for promoting the high-quality development of online international Chinese education.